Detailed ultrastructure of the Hirudo (Annelida: Hirudinea) salivary gland. (September 2020) - Saglam, Naim; Saunders, Ralph; Shain, Daniel H.; Saidel, William M.
Highlights: Salivary gland cells of Hirudo verbana embryos were physically separated. Adult salivary glands displayed highly developed cell bunches connected by fine channels. Channels from each salivary gland bunch combined to form larger canals that opened to the jaw. Abstract: Medical leeches have been widely used in medical applications and treatments for millennia. Studies on the salivary glands of blood-sucking leeches have focused on their bioactive secretions and mechanisms of action, with little attention to ultrastructure. In this study, we examined dissected embryonic and adult Hirudo verbana salivary glands by scanning electron microscopy (SEM). Gland cells of embryos were physically separated while adults displayed highly developed cell bunches in which each cell was connected to others by fine channels. Channels from each bunch combined to form a larger canal that opened to the jaw. Secreted material from these glands prevent blood from clotting and allow the adult to feed while sucking blood.